ANTIDEPRESSANT-LIKE ACTIVITY OF AQUEOUS EXTRACT OF ROSA DAMASCENA IN MICE - SHAIKH, JAMALUDDIN; WELI, AFAF MOHAMMED; SAID, SADRI ABDULLAH (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: Plant-based drugs have the potential to be very effective substitutes for prescription antidepressants. Rosa damascena has therapeutic potential as an analgesic, anticonvulsant, antitussive, bronchodilatory, antibacterial, anti-diabetic, anti-inflammatory, antioxidant, and laxative. Given this context, the goal of the current study was to assess Rosa damascena's potential antidepressant effects. Methods: Maceration was used to create an aqueous extract of Rosa damascena. The Tail Suspension Test (TST) on BALB/c mice and the Forced-Swimming test (FST) on C57BL/6 mice were used to quantify the antidepressant activity. Mice were divided into three groups: control (saline), standard (citalopram and desipramine), and Rosa damascena aqueous extract (n = 6 per group). Intraperitoneally (1 ml/100 g) injections of drugs were administered. Analysis of variance was used to examine the data, and then LSD post-hoc tests were performed. The data are expressed as mean±SEM. Results: Antidepressant-positive controls, citalopram and desipramine, significantly decreased the time of immobility in the FST and TST as compared to the vehicle control group (p<0.001). In FST, the immobility durations were significantly reduced by the Rosa damascena aqueous extract at a dose of 40 mg/kg compared to lesser doses of the same extract (10 and 20 mg/kg) (p<0.001). Similarly, the 40 mg/kg dose of Rosa damascena aqueous extract significantly reduced the length of immobility in TST (p<0.001). Conclusion: The present findings demonstrate Rosa damascena's antidepressant-like effects in mice. Further research is necessary to determine the underlying mechanism by which Rosa damascena generates effects akin to those of an antidepressant in light of this observation.